Teacher Motivation: A Case Study on What Motivates Expatriate Teachers at an English Medium Private School in Sharjah, United Arab Emirates - Carson, Lori Diane (2013)
While there have been many studies on what motivates students, research regarding motivating factors for teachers, particularly those that are expatriates, is limited. The lack of research in this area gave rise to this case study completed in a private English medium school in Sharjah, United Arab Emirates, a country whose education system lies almost entirely in the hands of foreign teachers. What motivates the expatriate staff as teachers, which groups of teachers are the most satisfied, and what factors motivate staff to remain teachers are explored. This study found several reasons expatriates come to the UAE: salaries without taxes, unemployment in their home countries, or spouses employed in the UAE. Others trained in other professions initially came to the UAE for different jobs, and then later became hired as teachers. Teachers participating in this study reported their main motivations for teaching as being primarily intrinsic, with more women than men stating their satisfaction with teaching. Also reporting greater satisfaction with teaching were those who initially wanted to be teachers and those with 5 or more years of professional teaching experience.